General and Greener Synthesis of Diverse Functional Organic Salts through Schiff Base Chemistry - Hu, Baoping; Shi, Qingrong; Lu, Feipeng; Zhang, Pengcheng; Peng, Panpan; Zhao, Chaofeng; Du, Yao; Su, Hui; Li, Shenghua; Pang, Siping; Nie, Fudie (Synlett, 2019)
We report a greener and more-general organic method for the synthesis of functional organic salts containing organic anions through a Schiff base reaction between readily available aldehydes and simple aminoguanidinium salts. This reaction is operationally simple, free of metal salts, and forms water as the sole byproduct. The broad scope and good functional-group compatibility of this method permit its use to provide ready access to a library of more than 70 distinct organic salts, including those of heterocyclic anions, complex pharmaceutical anions, and polyanions, which are difficult to obtain through classical inorganic methods. Moreover, choosing different aldehydes and organic anions provides a convenient method for modulating or improving the functional properties of the designed organic salts, such as their melting points, fluorescence, and energetic properties. We therefore expect that this method will open new opportunities for the discovery and functionalization of a wide variety of organic salts and functional materials.
Keywords: organic salts; Schiff base reaction; functional materials